Toward High-Performances of Halide Light-Emitting Diodes: The Importance of Ligands Engineering - Le Ma; Feijiu Wang (Inorganics, 2023)
Halide perovskite light-emitting diodes (PeLEDs) have attracted great attention because of their superior optical properties, such as extremely high photoluminescence (quantum yield up to nearly 100%) of active layers with tunable wavelengths over the entire visible spectral range. With a suitable modification of halide perovskites, carrier transport materials, and their interfaces, external quantum efficiencies exceeding 10%, 25%, and 20% have been achieved for blue-colored (465 nm), green-colored (512 nm), and red-colored (640 nm) LEDs, respectively. Many strategies for pursuing high performances of devices have been successfully demonstrated, among which ligand engineering has always played an important role in the active layer. Herein, we present a perspective to illustrate the effects and roles of the ligands in cesium lead bromide light-emitting diodes. This perspective is mainly classified into three parts: (1) ligands for CsPbBr3 LEDs could improve radiative recombination of perovskites and contribute to better efficiency of LEDs; (2) ligands could confine CsPbBr3 growth for blue emission of LEDs; (3) stabilities of materials and devices become better with ligand engineering. Finally, the summary and perspective on PeLEDs are highlighted and possible solutions are provided.